The Representation of Bereavements: A Surrealistic Analysis of Surviving Dead in Adrienne Kennedy’s She Talks to Beethoven - Abed, Hamid Hammad (Al-Adab Journal, 2023)
This study divulges the connection between the living and the dead individuals. Although the dead separated from the world of the living, they were unconsciously linked and remembered by some of the living people. The personal grief is the calamity that generates an expressive consequence to interrupt the person’s appropriate choice of the surrounded objects. Adrienne Kennedy, in She Talks to Beethoven, examines the furtive motives that dominate and govern the individual’s thinking and behaviour throughout certain critical state of mind.